Effects of nonsurgical periodontal therapy on leukocytes, erythrocytes and haemoglobin - Al-Bayati, Lina; Kamil, Wisam Alaa; Mohamed, Suhaila (2013)
Aim The aim of this study was to assess the outcome of the nonsurgical periodontal treatment in terms of its effect on leukocytes, erythrocytes and haemoglobin in consecutive subjects diagnosed with chronic periodontitis. Methods After obtaining the ethical approval from the ethics committee of the International Islamic University Malaysia, 25 systematically healthy Malaysian subjects diagnosed with chronic periodontitis were recruited for the study. Detailed oral hygiene instruction and standard periodontal therapy were performed. Full clinical periodontal parameters including full mouth plaque scores, bleeding on probing, pocket depth and clinical attachment loss were recorded and re-evaluated 3 months after the treatment completion. Blood samples were collected to determine the complete blood count at baseline and 3 months after the periodontal treatment. Results Nonsurgical periodontal therapy resulted in significant reduction in the white blood cells (WBC) where the average WBC decreased from 8.3 103/uL at baseline to 7.6 103/uL (p=0.038) after 3 months of periodontal therapy, and significant decrease in the monitored erythrocyte sedimentation rate (ESR) from 8.3 mm/hr to 5.9 mm/hr (p=0.033). However, the results of this study failed to show significant difference in the erythrocytes and haemoglobin (p>0.05) after the marked improvement in the scored clinical periodontal parameters in response to the periodontal therapy. Conclusion This study demonstrated that nonsurgical periodontal therapy results in a significant reduction in the white blood cells count and ESR.